Exploring Spiritual-Based Transformational Leadership Indicators in Palu City Hospital: A Qualitative Study - Kolomboy, Fajrillah; Rizkaningsih, Rizkaningsih; Syamsu, Andi Fatmawati (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Due to contextual issues, including social culture and pluralism, spiritual-based leadership in the nursing field has rarely received attention, resulting in comparatively few research projects. Whereas such research can lead to a spiritually supportive environment, benefiting the patients, nurses, and organizations. Current research aims to explore indicators of spiritual-based transformational leadership in Palu City Hospital. This research was done qualitatively through a grounded theory approach and Focus Group Discussion (FGD). In this case, 12 informants were chosen by purposive sampling. The instrument used was Focus Group Discussion (FGD) guidelines. In this study, the results of the FGD were analyzed using the N Vivo 12 Plus. Based on the qualitative data analysis results, a spiritual-based transformational leadership required three primary skill indicators, namely emotional skills, including emotional proficiency and emotional intelligence, spiritual skills including spiritual attitudes and spiritual intelligence, and social skills, namely being able to behave socially. For further research, it is necessary to carry out model intervention and model evaluation under new normal conditions and add other variable components such as performance and commitment.